The reality of School Ergonomics: A study on a sample of primary schools in the wilaya of Constantine - Benabderrahmane, Tahar; Chinoune, Sid ameur (Journal of Human Sciences, 2022)
The aim of this study is to uncover the reality of school ergonomics from the point of view of a sample of primary school teachers in the Wilaya  of Constantine.In order to achieve the objectives of the study, the researchers adopted the descriptive method. The researchers constructed a tool to measure the attitudes of the teachers towards the reality of school ergonomics. The tool consisted of (24) items belonging to four axes, which were applied to a sample of (47) teachers in some Constantine schools.The study found that school ergonomics is up to the required level from the point of view of the teachers through the dimensions: school buildings, classrooms, educational means, Physical Conditions.